Strategy implementation obstacles encountered by Malaysian engineering contractors - Zakaria, Mustafa; Dahalan, Hishamuddin; Ahmad, Norizan (2014)
Strategy implementation is one of the three fundamental components of the strategic management, besides strategy formulation and strategy evaluation and control. Strategy implementation is considered as most difficult because it affects the organizational culture, structure, resources and in fact the whole texture of an organization.Much of the studies on implementation indicate that the success rate of strategy implementation seems to be low. Despite, a review of the strategic management literature indicate that not much research emphasis given on the implementation side of strategy in Malaysia.This paper presents an attempt to examine strategy implementation among contractors registered with the Malaysian Department of Irrigation.More specifically this paper investigated the strategy implementation obstacles faced by the contractors. The population in this study consisted of personnel who had experience in handling problem projects of the Malaysian Irrigation Department. Structured interview and mail questionnaire were used to obtain data for the study.In this study the obstacles are broken down into eight dimensions which are purchasing, construction facility, human resource, finance, operations, management information system, sales, and environment. The three most challenging obstacles are those pertaining to the environment, management information systems, and human resource.